2020
DOI: 10.1109/tdei.2019.008379
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic / inorganic-organic nano-hybrid composites for thermally stable insulation of electrical wires. Part I: Composition and synthetic parameters

Abstract: Composite coatings comprising of particulate ceramic and silicon containing inorganicorganic nano-hybrids are synthesized and applied as high temperature capable coatings for electrical wire insulation. The nano-hybrids are synthesised from organosilanes bearing non-hydrolysable methyl, glycidyloxypropyl and phenyl groups. The molar ratios of organosilanes, acid catalysts and synthetic conditions are optimised to offer suitable mechanical and thermal performance to the composite coatings. Different particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The results showed that when the proportion of hollow glass microspheres in the filler was 20~40%, the coating showed excellent heat resistance. Pang Y X et al [61,62] conducted a detailed study of different organosilane compounds by designing and synthesizing a variety of nanocomposites. They finally selected a nanocomposite synthesized by MTMS, GPTMS, and PhTES to develop a ceramic/inorganic-organic nanocomposite.…”
Section: Organic-inorganic-composite High-temperature-resistant Elect...mentioning
confidence: 99%
“…The results showed that when the proportion of hollow glass microspheres in the filler was 20~40%, the coating showed excellent heat resistance. Pang Y X et al [61,62] conducted a detailed study of different organosilane compounds by designing and synthesizing a variety of nanocomposites. They finally selected a nanocomposite synthesized by MTMS, GPTMS, and PhTES to develop a ceramic/inorganic-organic nanocomposite.…”
Section: Organic-inorganic-composite High-temperature-resistant Elect...mentioning
confidence: 99%
“…The nodal temperatures, Tn, of the equivalent circuit, Fig. 3b, can be solved analytically using (6). The expression is validated against steady state thermal 3D Finite Element Analysis (FEA), Fig.…”
Section: Thermal Modelmentioning
confidence: 99%
“…1) minimise winding loss (AC and DC) 2) minimise non-active winding volume through use of concentrated coils or alternative machine topologies 3) raise electrical insulation temperature rating 4) enhance heat extraction (to dissipate loss) Incremental improvement across 1-4 can be achieved, for example, by adopting concentrated Litz wire windings, modem high-temperature insulation coatings with circa 240 °C temperature rating, [4]- [6], and liquid cooling of housings complemented by established end-winding cooling techniques, [7]. However, the step change in power-density needed calls for exploration of potentially disruptive technologies which can simultaneously address design goals 1-4 whilst ideally providing additional integration possibilities and value-add features, such as integrated terminals and routes to nondestructive disassembly and repair.…”
Section: Introductionmentioning
confidence: 99%